How useful are modeling approaches for resource-constrained scenarios? Accelerating crop breeding for a changing climate - CGIAR Research Program on Wheat (2021)
To what extent can breeding gains be achieved at a pace to contribute to climate change adaptation and food security? Scientists critically reviewed how crop modeling can assist their activities.